Surgical Site Infections and Antimicrobial Resistance Pattern - Chaudhary, Raskin; Thapa, Shrawan Kumar; Rana, Jid Chani; Shah, Pradeep Kumar (Journal of Nepal Health Research Council, 2017)
Background: Post-operative surgical site infections (SSIs) are among the leading cause of morbidity and increased medical expense. The aim of this study is to isolate identify and study antimicrobial susceptibility pattern of microorganism from surgical wound of admitted patients. Methods: This retrospective study was carried at the Microbiology Laboratory of Bharatpur hospital, Nepal, from May 2015 to October 2015. The pus samples were cultured and antibiotic susceptibility determined in vitro by Kirby Bauer’s disc diffusion method following clinical and Laboratory Standards Institute (CLSI) 2014 recommendation. Results: Of the total 250 samples, 194 (77.6%) showed bacterial growth. Staphylococcus aureus was 47.4% and Escherichia coli 20.60 %. Of 194 isolates 39.2% were multi drug resistant. Amikacin was sensitive in 93.1% of Gram positive isolates and 81.8% of gram negative isolates. Conclusions: Bacterial growth is common in surgical site. Staphylococcus aureus and Escherichia coli were multidrug resistant. Grampositive and gram negative isolates were commonly sensitive to Amikacin.